Polymorphism and White Light Emission of 1-Bromo-3,5,7-Triphenyladamantane compared with 1,3,5,7-Tetraphenyladamantane - Saravanan, Gowrisankar; Fokin, Andrey A.; Becker, Jonathan; Mathew, Neeshma; Schmedt auf der Günne, Jörn; Schreiner, Peter R; Justus Liebig University Giessen (My University, 2024)
Surprisingly, the crystal structures of bromophenyl adamantanes finely depend on two flavors of London dispersion (LD) interactions: relatively strong CH−π and quite weak Br⋯Br interactions. Here we report our investigation of 1-bromo-3,5,7-triphenyladamantane (1, BrAdPh3) and elucidation of two polymorphic crystal structures denoted as 1A and 1B using single crystal X-ray diffraction (SCXRD). In the monoclinic crystal system of 1A (P21/n space group), we observed CH−π interactions, while Br···Br interactions were absent. Conversely, the Br···Br interactions are a structure-defining factor in the formation of the monoclinic crystal system of 1B (R3 ̅ space group). To provide context, we compare our findings with 1,3,5,7-tetraphenyladamantane (2), characterized by numerous CH−π interactions orchestrating the molecules into chains in the solid. Both CH (phenyl) and CH2 (adamantane) groups thereby participate as dispersion energy donors (DEDs). Computational analyses were employed to investigate the interactions within the characteristic dimers present in the unit cells of 1A and 1B, including visualization of noncovalent interactions and the use of the atoms-in-molecules approach, and molecular orbital analysis. These support the notion of LD dimer-dimer interactions in 1A between the phenyl moieties, whereas 1B exhibits additional dimer-dimer Br···Br contacts. In contrast, the crystals of 2 are exclusively held together by CH−π stacking LD interactions, a feature absent in the polymorphs of 1. Both polymorphic forms of 1 emit white light when subjected to 900 nm continuous wave laser irradiation, displaying a subtle blue shift compared to 2. The absence of CH−π stacking interactions between the dimers of 1 causes a small red-shift in the emission spectrum. The NMR, SCXRD and Computation files are included in this dataset.
Keywords: ddc:540